Chemical effect of water addition on the ammonia combustion reaction. (1st July 2022) - Zhang, Qi; Zhou, Zhijun; Shan, Shiquan; Cai, Xichuan; Yang, Weijuan
Highlights: Influence of water addition on ammonia combustion reaction are studied via ReaxFF; Water addition is shown to promote the overall ammonia oxidation; H2 O enhances the conversion between NO and HNO at the middle stage of oxidation; The number of NOx molecules decreases with reduction of O2 concentration in O2 /H2 O environment. Abstract: Ammonia has become an emerging fuel. However, its combustion product NOx is polluting, and it is necessary to explore its conversion process. To determine the effect of water addition on ammonia oxidation and NOx, reaction molecular dynamics simulations are performed to study the chemical reactions of ammonia. Ammonia oxidation is studied in O2 /N2 and O2 /H2 O environments in a determining density and O2 /NH3 ratio equal under high temperature conditions. This work focuses on the initial reaction path of ammonia combustion established through chemical trajectory analysis. The ammonia oxidation behavior, the distribution of the main products, and the corresponding time evolution behavior on the atomic scale are also studied. Finally, the interconversion processes of molecules containing N elements in the ammonia oxidation products are analyzed. Results show that when N2 molecules are replaced by H2 O molecules, the formation of HNO increases with the net flux of the reactions: N H + O H → H 2 N O, H 2 N O → H + H N O . We also investigate the effect of different O2 concentrations. An increase of NO and HNO molecules with O2 concentration mainly from the reactions: O 2 + H → O + O H, H 3 N O + O H → H 2 N O + H 2 O, H 2 N O → H + H N O and H N O + O H → H 2 O + N O . In addition, the conversion affected by water addition between NO and HNO occurs mainly in the middle time of the oxidation, and H2 O enhances the severity of the oxidation with the number of OH radicals. Water addition provides a new way to control NOx emissions in ammonia combustion, that is, converting it into other H-containing compounds.